1987
DOI: 10.1152/jn.1987.58.1.180
|View full text |Cite
|
Sign up to set email alerts
|

Basic electrophysiological properties of spinal cord motoneurons during old age in the cat

Abstract: 1. The electrophysiological properties of alpha-motoneurons in old cats (14-15 yr) were compared with those of adult cats (1-3 yr). These properties were measured utilizing intracellular recording and stimulating techniques. 2. Unaltered in the old cat motoneurons were the membrane potential, action potential amplitude, and slopes of the initial segment (IS) and soma dendritic (SD) spikes, as well as the duration and amplitude of the action potential's afterhyperpolarization. 3. In contrast, the following chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
46
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 0 publications
10
46
0
Order By: Relevance
“…Although a suboptimal cortical drive cannot be discounted, the progressive decline in the instantaneous motor unit discharge frequency during the successive discharges at the onset of a fast contraction is consistent with the hypothesis of an age-related alteration in the intrinsic properties of motoneurons (17,31). This early decline in motoneuron discharge rate when the cell is activated by constant-current injection, which is known as spike frequency adaptation (8,20), could be modified by aging as it seems to be the case with chronic changes in physical activity levels (18).…”
supporting
confidence: 77%
“…Although a suboptimal cortical drive cannot be discounted, the progressive decline in the instantaneous motor unit discharge frequency during the successive discharges at the onset of a fast contraction is consistent with the hypothesis of an age-related alteration in the intrinsic properties of motoneurons (17,31). This early decline in motoneuron discharge rate when the cell is activated by constant-current injection, which is known as spike frequency adaptation (8,20), could be modified by aging as it seems to be the case with chronic changes in physical activity levels (18).…”
supporting
confidence: 77%
“…For example, motor neurons from older animals exhibit greater input resistance (Chase et al 1985;Kalmar et al 2009;Morales et al 1987), reduced rheobase current (Kalmar et al 2009;Morales et al 1987), and either longer (Cameron et al 1991;Kalmar et al 2009) or unchanged (Engelhardt et al 1989Morales et al 1987) AHP duration. Such parameters can be estimated only with indirect approaches in humans, such as the interval death rate analysis of single motor unit ISIs (Matthews 1996) or evaluation of the relation between the mean and SD of ISIs within a train of single motor unit action potentials (Piotrkiewicz et al 2007).…”
Section: Age-related Differences In Motor Unit Dischargementioning
confidence: 99%
“…Because recordings obtained from the same motor unit in a second set of data (n ϭ 12) were consistent with the larger set of data made from separate motor units (n ϭ 53), the difference in discharge characteristics for the two tasks was attributed to differences in the integration of synaptic input received by the motor neuron (Riley et al 2008). Given age-associated changes in both the synaptic input that is delivered to motor neurons (Boxer et al 1988;Eisen et al 1996;Oliviero et al 2006) and in the intrinsic properties of the motor neurons (Engelhardt et al 1989;Morales et al 1987;Piotrkiewicz et al 2007;Rossini et al 1992), it seems likely that the discharge characteristics of motor units at recruitment will differ for older adults when they perform such tasks. The purpose of the study was to compare the discharge characteristics of motor units recruited during an isometric contraction that was sustained with the elbow flexor muscles by older adults at target forces that were less than the recruitment threshold force of each isolated motor unit.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we have the first indication that in white matter myelin damage precedes axon loss, as the proportion of abnormal myelin profiles increases significantly in middle-aged animals compared to young animals. Disruption of myelin sheaths in the optic nerve is known to impair the conduction velocity of action potentials (Gutierrez et al, 1995), and an age-related reduction in axonal conduction velocity has been reported in several other systems (Aston-Jones et al, 1985;Morales et al, 1987;Xi et al, 1999). Reduction in conduction velocity might explain why the prevalence of myelin abnormalities in monkey prefrontal and visual cortex relates to the magnitude of age-related cognitive impairment Peters and Sethares, 2002), since the timing in neuronal circuits would thereby be altered with age.…”
Section: Conclusion and Functional Implicationsmentioning
confidence: 99%